THE IMPACTS OF ASSIMILATION ON SECOND-GENERATION BATAK-AMERICAN IMMIGRANTS' PERSPECTIVES TOWARDS BATAK GENDER NORMS - Clara Shinta Intan Berlian Cinta; Yusuf Kurniawan (Jurnal Penelitian Humaniora, 2022)
Batak is one of the patriarchal ethnic cultures in Indonesia that has strong gender norms applied within its people. Second-generation Indonesian Batak-American that live in both Batak gender norms and Egalitarian gender norms might have a different perspective about their ethnic gender norms as assimilation in America impacts their views. This research aims to find the impacts of assimilation toward Second-generation Batak-Americans in viewing Batak Ethnic gender norms. This research is digital ethnography. In analyzing the data, the research applies segmented assimilation by Portez and Zhou to answer the research questions. The result, assimilation impacts second-generation Batak-American immigrants’ perspective about Batak gender norms where they adapt more to the American Egalitarian gender norms and American Egalitarian family structure because of the human capitals that they have.